Beyond the punitive society operant conditioning : social and political aspects - Wheeler, Harvey 1918-2004; Center for the Study of Democratic Institutions (San Francisco W. H. Freeman and Company, 1973)
Papers presented at a symposium organized by J.H. Wheeler and sponsored by the Center for the Study of Democratic Instutions, held in Santa Barbara, CA.
Introduction: a nonpunitive world? / Harvey Wheeler -- The Skinnerian revolution / John R. Platt -- Behavioral technology and institutional transformation / Dennis C. Pirages -- Controlled environments for social change / Vitali Rozynko, Kenneth Swift, Josephine Swift, and Larney J. Boggs -- Operant behaviorism: fad, fact-ory, and fantasy? / Karl H. Pribram -- Great expectations / Arnold Toynbee -- Behaviorism's enlightened despotism / Chaim Perelman -- Some aversive responses to a would-be reinforcer / Max Black -- Can behavior be conditioned? / Robert Rosen -- How good is current behavioral theory? / John Wilkinson -- A system-theoretic view of behavior modification / L.A. Zadeh -- Questions / Fred Warner Neal -- Skinner and human differences / Arthur R. Jensen -- Skinner's new broom / Alexander Comfort -- Beyond B.F. Skinner / Lord Ritchie-Calder -- Skinner and "freedom and dignity" / Nathan Rotenstreich -- Is he really a grand inquisitor? / Michael Novak --- A quiver of queries / Joseph Schwab -- Answers for my critics / B.F. Skinner.
Papers presented at a symposium organized by J. H. Wheeler and sponsored by the Center for the Study of Democratic Institutions, held in Santa Barbara, Calif.
Includes bibliographical references (pages [267]-274)
Keywords: Skinner, B. F. -- 1904-1990.; Operant conditioning -- Congresses; Human behavior -- Congresses; Behaviorism (Psychology) -- Congresses